Avaliação clínica de restaurações reparadas por resina composta à base de silorano: estudo longitudinal randomizado controlado - Daniela Araujo Veloso (2011)
Purpose: To investigate clinical performance of defective conventional dimethacrylate-based composite resin restorations repaired by a low-shrinkage silorane-based composite or a dimethacrylate-based composite resin, at baseline, 6 and 12 months. Material and Methods: One hundred defective dimethacrylate-based composite resin restorations were repaired in this study. From those, 93 were examined at baseline, 91 at 6 months and 83 at 1 year. The restorations were randomly assigned to one of two treatment groups: Control (n = 50) Adper SE Plus, 3M /ESPE + Filtek P60 Posterior Restorative, 3M/ESPE and Test (n = 50) Repair with P90 System Adhesive Self-Etch Primer and Bond, 3M/ESPE and Filtek P90 Low Shrink Posterior Restorative, 3M/ESPE. Two calibrated examiners (Kw 0.78) evaluated all repaired restorations by direct observation, blindly and independently, at baseline, six months and at one year. The parameters examined were marginal adaptation, anatomic form, surface roughness, marginal discoloration, post-operative sensitivity and secondary caries. The restorations were classified as Alpha, Bravo or Charlie (Modified U.S. Public Health Service criteria). Mann-Whitney test compared the materials tested, for all clinical criteria, at baseline and at 6 and 12 months ( = 0.05). Wilcoxon test compared each material independently, for the same criteria, at baseline, and at 6 and 12 months ( = 0.05). Results: Drop-out in this study was about 9% after 6 months and 17% after 12 months. No statistically significant differences were found between the materials for all clinical criteria, at baseline and at 6 and 12-month recalls (p > 0.05). No statistically significant differences were found between the examination periods, when each composite resin was tested, for all clinical criteria (p > 0.05). Conclusions: After one-year evaluations, silorane-based composites exhibited a similar performance compared to dimethacrylate-based composites when used for making repairs. When proper planned, repairs may be an alternative restorative treatment to replacement of defective restorations with localized defects, but clinically acceptable, preserving healthy tooth structure, reducing costs and clinical time.